(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Soft tissue infections pose significant clinical challenges, particularly with the rise of methicillin-resistant Staphylococcus aureus (MRSA). This study aimed to investigate the epidemiological, microbiological, and treatment characteristics at a tertiary hospital in Southern Vietnam. Methods: A retrospective descriptive study was conducted on 469 patients with soft tissue infections treated at the Department of Orthopedic Trauma, University Medical Center Ho Chi Minh City, from January 2022 to December 2024. Results: Mean age was 53.6 ± 16.4 years; 56.5% were male; 47.8% had diabetes mellitus. Soft tissue abscess accounted for 55.7%; lower extremity involvement 77.4%. Culture-positive rate was 78.0%, yielding 524 bacterial isolates. MRSA comprised 90.1% of S. aureus strains and was present in 51.9% of culture-positive patients. Mean hospital stay was 13.0 ± 8.7 days; 96.8% required surgical intervention.Conclusions: The MRSA rate of 90.1% is among the highest reported globally. Empirical antibiotic regimens should prioritize MRSA coverage, and infection control measures should be strengthened.